2007
DOI: 10.1007/s10267-006-0338-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable fruit-body formation of edible mycorrhizal Tricholoma species for 3 years in open pot culture with pine seedling hosts

Abstract: Three edible mycorrhizal mushrooms, Tricholoma portentosum, T. saponaceum and T.terreum, that had formed ectomycorrhizas with Pinus densiflora seedlings in vitro, were maintained in open pot culture for three years under laboratory conditions. T. portentosum and T. saponaceum produced fruit bodies several times. For T. terreum, which produced a single fruit body in the third year, this is the first report of mushroom production under controlled conditions. Morphological observation of fruit bodies indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…The arbuscular mycorrhizal fungi Acaulospora laevis and Glomus mosseae (Schalamuk et al. 2006; Yamada et al. 2007) were also found in the Painted Gallery with a lower (1·5%) abundance.…”
Section: Discussionmentioning
confidence: 99%
“…The arbuscular mycorrhizal fungi Acaulospora laevis and Glomus mosseae (Schalamuk et al. 2006; Yamada et al. 2007) were also found in the Painted Gallery with a lower (1·5%) abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Basidiomata formation in ectomycorrhizal fungi is a complex phenomenon because a set of specific physical, nutritional and biotic factors is required, as well as the obligate dependency towards the host plant. In general, these conditions have been poorly studied in the case of edible ectomycorrhizal mushrooms (Kües and Liu, 2000;Wessels, 1993;Yamada et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that environmental conditions are crucial to basidioma formation in ectomycorrhizal fungi, including temperature, carbon dioxide concentrations in the atmosphere, moisture, salinity (Kües and Liu, 2000;Wessels, 1993), fertilization regime (Debaud and Gay, 1987;Godbout and Fortin, 1990), relative humidity (Yamada et al, 2007), the contribution of host carbohydrates (Lamhamedi et al, 1994), and the abundance of ectomycorrhizal colonization of the fungal species of interest (Guerin-Laguette et al, 2013;2014;Pilz and Molina, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gray is one of the well-known edible ectomycorrhizal (ECM) fungi with a worldwide distribution. Over the course of past decades, assessment of ECM fungal sporocarp production has been carried out, and some pot culture trials have been conducted to determine the golden edible ECM fungal growth, primordium, and basidiocarp formation (Yamada et al 2001(Yamada et al , 2007, which are greatly influenced by various factors such as fatty acids (Unestam and Sun 1995), wood ash (Hagerberg and Wallander 2002), surfactants or vegetable oil (GuerinLaguette et al 2003), and microbial interaction (Gamalero et al 2003). Among these factors, much attention has been devoted to the bioactive compounds that improve the process of mycelial growth (Unestam and Sun 1995).…”
mentioning
confidence: 99%